Dampak Moratorium Hutan Terhadap Ekonomi Indonesia : Analisis Menggunakan Model IRSA-Indonesia 5 - Rakhmindyarto, Rakhmindyarto (Badan kebijakan Fiskal, 2012)
This paper discusses the economic effects of the forest moratorium policy which has been launched by the government through the Presidential Decree no. 10 of 2011 dated 20th of May 2011. The issues addressed in the paper are the impacts on: land uses and natural forest area, carbon emissions, domestic prices, export-import, GDP, and poverty rate. Using the quantitative method of IRSA-Indonesia 5 - an inter-regional CGE model, the results show that the forest moratorium policy has both positive and negative impacts on Indonesia's economy.